Implementation of carbon emission reduction and green innovation on investor reaction with environmental performance as a moderation variable - Vannia, Jesslyn; Lindrianasari, Lindrianasari (Edelweiss Applied Science and Technology, 2025)
This research aims to explores the relationship between carbon emission reduction, green innovation, and investor reaction, with environmental performance acting as a moderating factor. Carbon accounting plays a vital role in tracking emissions and evaluating the success of environmental initiatives. Companies that demonstrate efforts to reduce their company's carbon emissions and implement green innovations to demonstrate their commitment to sustainability can reduce investment risks, thereby attracting investors to invest in the company. The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2023, using a purposive sampling method. The research data utilized are secondary data in the form of annual reports obtained from the IDX website. The analytical method used is multiple linear regression analysis. The research results show that carbon emissions reduction and green innovation significantly negatively affects investor reactions. This is because there is still very little socialization from the company regarding operational activities in the environment towards the community as shareholders. Meanwhile, environmental performance could moderate the effect of carbon emission reduction and green innovation on investor reactions.